Studi Fenomenologi Stunting pada Balita 24-59 Bulan di Wilayah Kerja Puskesmas Tlogomulyo Kabupaten Temanggung - Isfaizah; Siswati (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2023)
The prevalence of stunting in Temanggung Regency is 28.9% and it is ranked 2nd in Central Java. Many factors influence the incidence of stunting, both direct and indirect. This research aims to determine the phenomenon of stunting in toddlers aged 24-59 months in the Tlogomulyo Community Health Center Working Area. This research method is qualitative descriptive research with a phenomenological approach. The population was 145 stunted mothers of toddlers and a sample of 3 stunted mothers of toddlers. The sampling technique used purposive sampling technique. Data collection using in-depth interviews, observation and documentation. Data analysis using the Miles & Huberman technique. Description of the phenomenon of stunting in toddlers 24-59 months, namely 3 stunted toddlers who have received a diagnosis from a pediatrician. Things related to the incidence of stunting include maternal weight gain during pregnancy, hyperemesis gravidarum, and maternal tea/coffee consumption during pregnancy, maternal knowledge about nutrition and Feeding Practices for Infants and Children. Several things related to the incidence of stunting include weight gain during pregnancy, hyperemesis gravidarum, tea/coffee consumption during pregnancy, maternal knowledge about nutrition and feeding practices for babies and children. Researchers recommend that all pregnant women must pay attention to nutrition during pregnancy and after the baby is born, they must be given MP ASI with a 4 star menu to minimize the incidence of stunting. Abstrak Prevalensi stunting di Kabupaten Temanggung sebesar 28,9% dan menduduki peringkat ke-2 di Jawa Tengah. Banyak faktor yang mempengaruhi kejadian stunting baik faktor langsung maupun tidak langsung. Tujuan dari penelitian ini untuk mengetahui fenomena kejadian stunting pada balita 24- 59 bulan di Wilayah Kerja Puskesmas Tlogomulyo. Penelitian ini merupakan penelitian diskriptif kualitatif dengan pendekatan fenomenologi. Populasi 145 ibu balita stunted dan sampel 3 ibu balita stunting.Tehnik sampling menggunakan tehnik purposive sampling. Pengumpulan data dengan wawancara mendalam, observasi dan dokumentasi. Analisa data dengan tehnik Miles & Huberman. Gambaran fenomena kejadian stunting pada balita 24-59 bulan yaitu 3 balita stunting sudah mendapatkan diagnosa dari Dokter Spesialis Anak. Hal yang berkaitan dengan kejadian stunting meliputi penambahan berat badan ibu saat hamil, hiperemesis gravidarum, dan konsumsi teh/ kopi ibu selama hamil, pengetahuan ibu tentang gizi dan Praktik Pemberian Makan pada Bayi dan Anak. Beberapa hal yang berkaitan dengan kejadian stunting berupa  penambahan BB saat hamil, hiperemesis gravidarum, konsumsi teh/kopi selama hamil, pengetahuan ibu tentang gizi dan Praktik Pemberian Makan pada Bayi dan Anak. Peneliti menyarankan untuk seluruh ibu hamil harus memperhatikan gizi saat hamil dan setelah bayi lahir harus diberikan MP ASI dengan menu 4 bintang untuk meminimalisir kejadian stunting